On the geopragmatics of anthropological identification - Chun, Allen John Uck Lun, 1952- (Loose can(n)ons ;, 2019)
On the Geopragmatics of Anthropological Identification explores the discursive spaces of our speaking position, or what has routinely been referred to in the literature as the poetics and politics of writing culture. At issue here are its problematic underlying notions of cultural identity, authorial subjectivity and postcolonial critique. Contrary to the widespread assumption that cultural studies and the social sciences share a common discourse of culture and society, Allen Chun argues that 'modern' disciplinary practices and axioms have in fact produced inherently incompatible theories. Anthropology's ethical relativism has also created obstacles for a critical theory of culture and society.